A Clinical Case of Scrub Typhus in the United States Forces Korea Patient with Eschar and Genetic Identification of Orientia tsutsugamushi Using Multiplex PCR-Based Next-Generation Sequencing - Seungchan Cho; Jon C. Allison; Kkothanahreum Park; Jin Sun No; Seung-Ho Lee; Kyungmin Park; Jongwoo Kim; Terry A. Klein; Heung-Chul Kim; Won-Keun Kim; Jin-Won Song (Pathogens, 2021)
An epidemiological investigation was conducted for a scrub typhus case reported in a U.S. Forces Korea military patient in the Republic of Korea in November 2018. The patient had a fever, maculopapular rash, and an eschar. The full-length sequence of Orientia tsutsugamushi 56-kDa type-specific antigen (TSA) gene was obtained from eschar tissue by multiplex PCR-based Next Generation Sequencing for genetic identification. Based on the 56-kDa TSA gene, the O. tsutsugamushi aligned most closely with the Boryong strain.